SAHAM DAN PASAR MODAL SYARIAH : KONSEP, SEJARAH, DAN PERKEMBANGANNYA - Fadlillah; Achmad Tarmidzi Anas; Badrut Ali; Badrus Sofi; Lukman; M. Samsul Arifin (ICO EDUSHA, 2023)
The Shariah capital market is growing, as demonstrated by the rise in the stock index in the Jakarta Islamic Index (JII). This index collects the price of shares of thirty companies that conform to the Islamic shariah and uses a scale of performance based on the sharia, one of which is the beta of sharial shares. Therefore, this study aims to analyze Sharia capital markets, including stocks. This empirical research uses purposive sampling techniques. Data obtained through the analysis of companies whose shares are listed on the Jakarta Islamic Index. History, Ideas, and Development of the Stock Market and the Syri'ah This is an attempt to provide a description of the capital market and limited stocks from a Syrian point of view. Therefore, this study aims to explain how it is applied in the financial sphere in other countries such as the United States, Malaysia and Indonesia. Keywords: Capital Market, Shares, Sharia Finance References   Agutianto, “ Mengenal Konsep Pasar Modal Syari’ah,’ http:// agustianto. niriah.com/2008/04/30 mengenal konsep-konsep pasar modal syari’ah. Ahmad Kamil , M. Fauzan , Kitab Undang-Undang Hukum Perbangkan dan Ekonomi Syari’ah, (Jakarta: Kencana,2007), 756 Ayub, M. (2007). "Islamic Banking and Finance: An Integrative Approach." Pearson Education. Buku ini memberikan wawasan tentang sistem keuangan Islam sebagai alternatif dalam konteks global. Aziz Budi Setiawan, “Perkembalngan Pasar Modal Syariah”, dalam http://www.iei.or.id/ Dahlan siamat, manajemen lembaga keuangan (Jakarta: LP FEUI, 2001), 268. Dahlan Siamat, Manajemin  268. Financial Stability Board. (2020). "Global Shadow Banking Monitoring Report." (Laporan yang mencakup perkembangan sektor keuangan, termasuk lembaga keuangan non bank). Hafiza, A., & Zulkarnain, A. (2017). "Islamic Stock Market Performance: Case of FTSE EMAS Shariah Index." Procedia Economics and Finance, 37, 49-54. https://ojk.go.id/id/kanal/pasar-modal/pages/syariah.aspx Hug T. Patrick, U Tun Wai, “ Stocks and Bond Issues, and Capital Markets in Less Developed Countries,” IMF Papern,1973, 4. Iqbal, M., & Mirakhor, A. (2007). "An Introduction to Islamic Finance." John Wiley & Sons. (Buku yang memberikan pemahaman dasar tentang keuangan syariah dan instrumen keuangan Islam). John Black, Oxford A Dictonary Economics (New York:Oxford University press, 1998),51. Kamil , M.Fauzan, Kitab Undang-Undang, 482 dan 756. Kompas, Apa Itu Saham: Definisi, Jenis, Keuntungan, Risiko, dan Cara Membeli, Dalam https://amp.kompas.com/money/read/2021/03/09/235100626/apa-itu-saham-definisi-jenis-keuntungan-risiko-dan-cara-membeli 09, Peninjauan ulang terhadap saham-saham syari’ah dilakkan pada bulan April dan Oktober setia tahunnya. Lihat The Islamic Capital Market http:// www.klse.com.my/website /bm/products and services. Rushdi Siddiqui, Islamic Indexes: The DJIM Framework dalam Suhail Jaffer (ed.),Islamic Asset Management (UK: Euromoney books, 2004),1. Syed Othmat Alhabshi, (Development of Capital Market under Islamic Prinipeles), 2008.